Web-based cyber counselling system in supporting the implementation of the “merdeka belajar-kampus merdeka (MBKM)” curriculum in university - Hidayat, Rahmat; Kusen, Kusen; Risdianto, Eko (Universitas Islam Negeri Raden Intan Lampung, 2022)
In the 4.0 era, it is required to use technology in all aspects of education, including in the field of counselling. So it is necessary to develop an online counselling system or cyber counselling and to be able to carry out development, it is necessary to analyze student perceptions about the importance of developing a cyber counselling system. Therefore, this study aims to determine the importance of developing a web-based cyber counselling system in supporting the implementation of the MBKM curriculum in universities. This type of research is survey research using quantitative research methods. The population in this study were all guidance and counselling students at IAIN Curup and UIN Mahmud Yunus Batusangkar. However, the research sample was 34 students who were representatives of the 2 universities. The study was conducted in August 2022. The data collection technique used a questionnaire so the measuring instrument was a questionnaire made with a modified Likert scale with 4 answer choices, namely strongly agree, agree, disagree, and strongly disagree, which were then analyzed quantitatively and the results were described. The results of the study show that students strongly agree that the development of a web-based cyber counselling system is essential in supporting the implementation of the MBKM curriculum in universities. This research can contribute to other research on what kind of cyber counselling system can be developed to suit the needs of students.